A Understanding career calling: historical roots and practical relevance for school counselors - Alfan, Robbani; Solehuddin, M; Nurihsan, Juntika; Riksa Yustiana, Yusi (Indonesian Institute for Counseling, Education and Therapy (IICET), 2024)
This article critically examines the origins and evolution of the term